Functional diversification of duplicated chalcone synthase genes in anthocyanin biosynthesis of Gerbera hybrida. Issue 4 (25th November 2013) - Deng, Xianbao; Bashandy, Hany; Ainasoja, Miia; Kontturi, Juha; Pietiäinen, Milla; Laitinen, Roosa A. E.; Albert, Victor A.; Valkonen, Jari P. T.; Elomaa, Paula; Teeri, Teemu H.
Summary: Chalcone synthase (CHS) is the key enzyme in the first committed step of the flavonoid biosynthetic pathway and catalyzes the stepwise condensation of 4‐coumaroyl‐CoA and malonyl‐CoA to naringenin chalcone. In plants, CHS is often encoded by a small family of genes that are temporally and spatially regulated. Our earlier studies have shown that GCHS4 is highly activated by ectopic expression of an MYB‐type regulator GMYB10 in gerbera ( Gerbera hybrida ). The tissue‐ and development‐specific expression patterns of three gerbera CHS genes were examined. Virus‐induced gene silencing (VIGS) was used to knock down GCHS1 and GCHS4 separately in gerbera inflorescences. Our data show that GCHS4 is the only CHS encoding gene that is expressed in the cyanidin‐pigmented vegetative tissues of gerbera cv Terraregina. GCHS3 expression is pronounced in the pappus bristles of the flowers. Expression of both GCHS1 and GCHS4 is high in the epidermal cells of gerbera petals, but only GCHS1 is contributing to flavonoid biosynthesis. Gerbera contains a family of three CHS encoding genes showing different spatial and temporal regulation. GCHS4 expression in gerbera petals is regulated post‐transcriptionally, at the level of either translation elongation or protein stability.